Leadership and Management in Science and Technology: Competency Model - O. V. Vorobyeva; E. M. Ivannikova; V. V. Malandin; D. S. Sekirinsky; E. V. Karavaeva; A. I. Suleymanova; I. G. Teleshova (Высшее образование в России)
The article deals with scientific and methodological substantiation and description of the competency model of a modern leader and manager in scientific and technological sphere. This model has been developed by the authors on the initiative of the Coordinating Council for Youth Affairs in Scientific and Educational Spheres of the Presidential Council for Science and Education in the framework of the managers’ contest “Leaders of Russia” (specialization “Science”, season 2019– 2020). The competency model is aimed at improving the efficiency of solving the problems of scientific and technological development of Russia by overcoming the lack of personnel which is ready not only to conduct research at the world level, but also to take responsibility for the formation of priorities for scientific and technological development that meet the interests of Russia, as well as for their implementation. The proposed model is the first of its kind developed and tested system of competencies for improving leadership and management potential of Russian science.